Titles change the esthetic appreciations of paintings - Gerger, Gernot; Leder, Helmut (Frontiers in Human Neuroscience, 2015)
Aesthetic experiences of artworks are influenced by contextualizing information such as titles. However, how titles contribute to positive aesthetic experiences is still an open issue. Considering that fluency, as well as effortful elaborate processing, potentially influence aesthetic experiences, we tested how three different title types—semantically matching (fluent), semantically non-matching (non-fluent), and an “untitled” condition (control)—affected experiences of abstract, semi-abstract, and representational art. While participants viewed title/artwork combinations we assessed facial electromygraphic (fEMG) recordings over M. corrugator supercilii and M. zygomaticus major muscle to capture subtle changes in emotional and cognitive processing, and asked for subjective liking and interest. Matching titles, but also the more effortful untitled condition, produced higher liking compared to non-fluently processed, non-matching titles especially in abstract art. These results were reflected in fEMG with stronger M. corrugator activations in the non-matching condition followed by the untitled condition. This implies high cognitive effort as well as negative emotions. Only in the matching condition, M. zygomaticus was more strongly activated indicating positive emotions due to fluency. Interest, however, was hardly affected. These results show that high levels of dis-fluency and cognitive effort reduce liking. However, fluency as well as moderate levels of effort contribute to more positive aesthetic experiences.